VALUE CHAIN UPGRADING: EVIDENCE FROM SMOKED FISH AGRIBUSINESS IN CENTRAL JAVA - Wicaksana, Indrajit; Nurmalina, Rita; Suprehatin, Suprehatin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
Smoked fish is one of the processed fish products that provided higer added value. However, there are still great opportunities to increase added value of smoked fish products through upgrading their value chains to make them more competitive and sustainable. This study aims to examine value chain upgrading of the smoked fish in Central Java. The data were obtained from 52 smoked fish value chain actors in Central Java by conducting in-depth interviews. The data was analyzed using a qualitative descriptive analysis of value chain upgrading. The results showed that the smoked fish value chain in Central Java can be upgraded through three upgrading types: product, process, and functional. Product upgrading can be done by using vacuum packaging and food boxes for processors and food stallers respectively. Process upgrading can be done by adopting fish detection technology (for fisherman) and administrative system applications (for wholesalers and traders). Functional upgrading can be improved by implementing direct selling from processors to restaurants and online marketing for retailers. As these upgrading activites will require additional costs, the smoked fish value chain actors need to consider the costs to get higher benefits in the implementation of value chain upgrading for smoked fish in Central Java.